Investigation on distribution characteristics of flexible biomass particles in a fluidized bed riser. (1st July 2020) - Geng, Fan; Teng, Haixu; Gui, Changgeng; Wang, Yingchao; Yuan, Longji; Yang, Yingying; Xu, Dayong
Graphical abstract: Spatial distributions of cut tobacco particles in the riser. Highlights: Flexible biomass particles were investigated by a 3D chain model. Impulse-momentum theorem, Routh-Poisson method and Coulumb friction for collision. Dynamic characteristics of particles were visually analyzed at particle-scale. 3D particle concentrations were provided to discriminate particle clusters. Abstract: The heterogeneous properties of biomass particles make their processing difficult in the fluidized beds. To handle biomass particles more easily, the fluidization process of the flexible biomass particles in a cold fluidized bed riser was investigated in the present study. The behavior of biomass particles subjected to the air flow was studied via the Euler-Lagrange method. Meanwhile, the particles were analyzed via a 3D particle model, and the collision was considered based on the impulse-momentum theorem, Routh-Poisson method and Coulumb's law of friction. The dynamic characteristics of the simulated particles, the particle distribution and the bending degree were first presented and validate the established model and the analysis with relevant experimental data. Then the fluidization processes of flexible biomass particles were analyzed under different air velocities and feeding rates. The obtained results indicated that particle distribution in the riser is uneven, and it has the bottom-dense and up-dilute characteristic in the axial direction and the central-dilute and near-wall-dense characteristic in the transverse direction. The flexible particles mainly present the bending patterns during the fluidization. The particle concentration presents regular variation under different conditions. The present method is valid to predict the dynamic behavior of flexible biomass particles, and paves a useful way to understand the treatment process of non-spherical particles.